2008
DOI: 10.1007/s00531-008-0306-3
|View full text |Cite
|
Sign up to set email alerts
|

Ophiolitic detritus in Cretaceous clastic formations of the Dinarides (NW Croatia): evidence from Cr-spinel chemistry

Abstract: Cr-spinel is a common heavy mineral in the sandstones of Cretaceous synorogenic sedimentary formations of the NW Dinarides, Croatia. The rocks occur in isolated exposures in the uplifted basement units of Medvednica, Ivanščica, Ž umberak and Samobor Mountains near Zagreb. In this area, evidence of the early Alpine evolution of the Dinarides is obscured due to strong dismemberment of pre-Tertiary tectonostratigraphic units resulting from an intense tectonic history, as well as due to the widespread sedimentary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Harzburgitic sources vastly predominate in most of the Cre- taceous synorogenic flysches all over the Alpine-CarpathianDinaridic belt (Pober & Faupl 1988;Árgyelán 1996;von Eynatten & Gaupp 1999;Jablonský et al 2001;Lužar-Oberiter et al 2009). There are some cases described in literature which showed that the Mg/(Mg+ Fe 2+ ) vs. Cr/(Cr + Al) provenance diagrams of Dick & Bullen (1984) and Pober & Faupl (1988) are not necessarily valid for all spinel sources.…”
Section: Discussionmentioning
confidence: 99%
“…Harzburgitic sources vastly predominate in most of the Cre- taceous synorogenic flysches all over the Alpine-CarpathianDinaridic belt (Pober & Faupl 1988;Árgyelán 1996;von Eynatten & Gaupp 1999;Jablonský et al 2001;Lužar-Oberiter et al 2009). There are some cases described in literature which showed that the Mg/(Mg+ Fe 2+ ) vs. Cr/(Cr + Al) provenance diagrams of Dick & Bullen (1984) and Pober & Faupl (1988) are not necessarily valid for all spinel sources.…”
Section: Discussionmentioning
confidence: 99%
“…Cr-bearing spinels have been considered important petrogenetic indicators by many authors [65][66][67][68][69][70][71], due to their chemical variability in parental melt composition and/or crystallization conditions in igneous rocks, and as paleogeographic indicators in geodynamic reconstructions, because of their resistance to mechanical stress, weathering and diagenesis in sedimentary environments. Commonly-used diagrams for these purposes are the Cr# vs. Mg# and the TiO 2 vs. Al 2 O 3 [3,5] as well as the Cr-Fe 3+ -Al ternary plot.…”
Section: Thermometric Considerations and Oxidation Evaluationmentioning
confidence: 99%
“…Cr-spi nels orig i nat ing from cu mu late and ex tru sive volca nic rocks tend to have higher TiO 2 (Kamenetsky et al, 2001). High Fe 3+ and TiO 2 , along with lower Mg#, sug gest that the Cr-spi nels could have been the prod ucts of frac tional crystallisation and re-equil i bra tion at lower tem per a tures due to slow cool ing (Arai, 1992;Kamenetsky et al, 2001;Lužar-Oberiter et al, 2009), and thus prob a bly de rived from cumu late mem bers of an ophiolite source. The in creased con tents of TiO 2 in most Cr-spi nels from the Malcov Fm.…”
Section: Heavy Minerals and Their Possible Originmentioning
confidence: 99%